(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated work environment, workload and lecturers’ performance in Nigerian Universities. The descriptive design of the survey type was selected for the study. Data was collected to illustrate the current situation regarding work environment, workload and lecturers’ performance in Unilorin and Kwara State University. The population of the study was made of 985 lecturers. Four hundred (400) respondents were selected as sample size using purposive sampling and simple random sampling techniques were used. The instrument used was tagged ‘Work Environment, Workload and Lecturers’ Performance Questionnaire’ (WEWLALPQ). The instrument used for the study was subjected to screening by expert for face and content validity, the expert determined the face level of appropriateness of the instrument in measuring what it purport to measure and ensure that it contain appropriate items that could actually elicit the intended responses. The reliability of the instrument was determined using a pilot test. The instrument was administered to 60 lecturers outside the study area. The instrument was administered twice within an interval of two weeks. Data collected was analyzed using Pearson Product Moment Correlation Statistics. Reliability Coefficients of 0.81 was obtained. The co-efficient value was high enough to make the instrument reliable and useful for the study. Data collected was analyzed using descriptive statistics. Findings of the study revealed a moderate work environment and lecturer performance. Also, lecturer workload plays a moderate role in their level of performance. The study recommended based on this result that, lecturers should not be over loaded with work and duties in other to increase their performance. The university administrators should employ more lecturers and improve the provision of facilities to reduce the workload of the available lecturers and support the safety and convenience of the work environment.